Impact on the Performance of Health Workers Adopted Performance-Related Contracts in the Provision of Basic Public Health Service at Village and Township Levels - Liang Zhang; Shuangbao Xie; Jian Wu; Zhen'ang Huo; Yaojun Zhao; Zhanchun Feng (Tehran University of Medical Sciences, 2013)
Background: This paper focus on the impact on the performance of health workers at village and township levels in the provision of a government stipulated package of basic public health service, which adopted the performance-related contracts mode. Methods: The concept of balanced scorecard was adopted and developed to gather the 11 evaluation indicators distributed in four quadrants. These were implemented using on-site questionnaire and interview design. Four thousand and twenty-one respondents at 30 administrative villages including 2674 respondents at 20 pilot villages and 1347 at 10 control villages were investigated. Meanwhile, 62 administration officials from three counties and nine townships were interviewed. Results: Eight of 11 evaluation indicators were obviously better in pilot counties than in Control County, The remaining three indicators respectively represented that equal, inferior to control county, and could not clear judge. Conclusion: The performance of health workers at village and township levels in the provision of basic public health service in pilot counties, which adopted the performance-related contracts mode, is better than before and control county.